Diagnostic Immunization with Bacteriophage ΦX 174 in Patients with Common Variable Immunodeficiency/Hypogammaglobulinemia - Smith, Lauren L.; Buckley, Rebecca; Lugar, Patricia (Frontiers in Immunology, 2014)
Purpose: Use of the T cell-dependent neoantigen bacteriophage ΦX 174 has been described since the 1960s as a method to assess specific antibody response in patients with primary immunodeficiencies. We reviewed a cohort of patients at Duke University Medical Center (DUMC) who received immunization with bacteriophage and report the clinical utility and safety of the immunization, as well as patient characteristics. Methods: A retrospective chart review was performed of all Duke Immunology Clinic patients (pediatric and adult) who received immunizations with bacteriophage, from 1976-2012. Subjects were selected for inclusion if their diagnosis at the time of bacteriophage was either presumed or confirmed common variable immunodeficiency (CVID), hypogammaglobulinemia, transient hypogammaglobulinemia, or antibody deficiency unspecified. Follow up post-immunization was also recorded. Results: One hundred twenty-six patients were identified, 36 adult and 90 pediatric patients. Diagnoses prior to bacteriophage were CVID (n=100), hypogammaglobulinemia (n=23), and antibody deficiency (n=3). Post-immunization diagnoses were CVID (n=65), hypogammaglobulinemia (n=19), unknown (n=23), no primary immune deficiency (n=10), and other primary immunodeficiency (n=9). Seventy-five patients had abnormal bacteriophage results, 37 were normal, and 14 were borderline. There were 257 recorded administrations of the immunization. Information was available on adverse reactions for 171 administrations. Fourteen immunizations were associated with minor adverse events. Nineteen patients stopped their immunoglobulin replacement therapy based on reported normal responses to immunization. Conclusions: Bacteriophage ΦX 174 immunization is a safe, well-tolerated, and clinically useful method to assess antibody response in patients with suspected antibody-mediated immunodeficiencies, particularly those who are on immunoglobulin replacement therapy at the time of immunization